HUBUNGAN TINGKAT PENGETAHUAN KOGNITIF DENGAN KEMAUAN MELAKUKAN CARDIOPULMONARY RESUSCITATION (CPR) PADA REMAJA DI SMAN MALANG - Rahmawati Maulidia; Nining Loura (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2019)
The action that connects survivors of cardiac arrest is called the Chain of Survival. Chain of Survival. The role of CPR bystander is very important to save cardiac arrest victims, therefore training and knowledge about CPR are being disseminated to ordinary people including in Indonesia. According to a preliminary study obtained by researchers, education about basic life assistance has been taught in several state high schools in Malang, especially in material taught at the Youth Red Cross (PMR). The purpose of this study is to to determine the relationship of cognitive knowledge level with the willingness to perform cardiopulmonary resuscitation (CPR) in adolescents in poor public high schools. Method In this research, This study used a correlational analytic design with a crossectional approach to determine the relationship of cognitive knowledge level with the willingness to perform cardiopulmonary resuscitation (CPR) in adolescents. The study sample consisted of 76 respondents. The sampling technique uses cluster sampling. The inclusion criteria for nurses were as follows: PMR members in Malang State High School who were still active, students who were willing to become respondents. While the exclusion criteria: students who are not present at the time of data collection and experience disability / disability. The independent variable of this study is the level of cognitive knowledge while the dependent variable is the willingness to do. The instrument in this study used a questionnaire CPR. Statistical results using the Chi Square test show that the p value is 0.002 (<0.05). This shows that there is a relationship between the level of cognitive knowledge and the willingness to do CPR in adolescents in Malang Senior High School. The better the cognitive cognitive level of a person, the higher a person's willingness to do CPR. Willingness to do CPR will help in minimizing the incidence of cardiac arrest in the community. Keywords: Cardiopulmonary Resuscitation (CPR), Willingness, Level of Cognitive Knowledge